NAFKAH PRODUKTIF UNTUK ANAK PERSPEKTIF KIAI SYANSURI BADAWI - Yayan Musthofa; Mohamad Anang Firdaus (Asy-Syari'ah, 2022)
The obligation of parents to provide for their children at least until they reach adulthood, which is 21 years referring to the KHI policy article 98 paragraph (1), when they are married, or have entered ar-rusydu phase (understanding the law and independence) referring to classical fiqh studies. In another study on maqāshid as-syarī'ah version, when the child has entered the age of 23 years based on the calculation finishing study period plus a year of financial independence trial period. In order to study further to prepare children's financial independence, this study aims to examine more deeply the concept of productive livelihood from the maqāsid as-syarī'ah perspective in the book of Fiqh Al-Munākaḥāt by Kiai Syansuri Badawi. This article includes a literature review with the maqāsid as-syarī'ah approach of Jasser Auda, while the object of this study is the work of Kiai Syansuri Badawi. From this research, I found that livelihood in Kiai Syansuri Badawi's view contains a productive meaning or a productive spirit and is in accordance with Jasser Auda's maqāshid as-syarī'ah concept for human development as the goal of the Shari'a. This article is important to build human development –especially Muslims– with the disteribution and management of a productive living, starting from the smallest organization, namely the family.